2002
DOI: 10.1063/1.1495525
|View full text |Cite
|
Sign up to set email alerts
|

Role of the wetting layer in the carrier relaxation in quantum dots

Abstract: We present picosecond time resolved photoluminescence measurements of GaAs/AlGaAs quantum dot structures-grown by modified droplet epitaxy-where no wetting layer is connecting the dots. We find a fast carrier relaxation time ͑30 ps͒ to the dot ground state, which becomes even faster for increasing the photogenerated carrier injection. This shows that the two-dimensional character of the wetting layer is not relevant in determining the quantum dot capture, in contrast with the conclusions of several models so f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 20 publications
5
39
0
Order By: Relevance
“…The rise time values decrease with a 1 / P dependence, with P the excitation density, which is common for a two-particle scattering process. 10,32 From these measurements it is clear, that the carrier capture process is dominated by different mechanisms for the two density regimes. The results as depicted in Fig.…”
Section: Excitation Density Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…The rise time values decrease with a 1 / P dependence, with P the excitation density, which is common for a two-particle scattering process. 10,32 From these measurements it is clear, that the carrier capture process is dominated by different mechanisms for the two density regimes. The results as depicted in Fig.…”
Section: Excitation Density Dependencementioning
confidence: 99%
“…1 showing the single LOphonon line at the onset of the continuum background, in accordance with observed PLE spectra. 1,6,7 Despite intensive investigations on the carrier capture and relaxation in QDs, the various explanations 1,10,11,[14][15][16][17][18] for the relaxation channel which have been proposed do not provide a single coherent picture. In particular, a clear consensus for the detailed carrier relaxation mechanism is still lacking.…”
Section: Continuum Relaxation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…We do not expect the Al content of the barrier to influence the obtained GaAs nanostructure morphology as the AlGaAs barrier is buried under a 1.75 ML GaAs top layer which forms on the surface during the following Ga deposition step 6,32 . Prior to the deposition of Ga, the As cell is closed and the background pressure reduced below 10 −9 Torr.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…The captured carriers then relax into the lower lying quantum ring levels where they radiatively recombine. Our previous study showed the recombination lifetime in GaAs/(Al,Ga)As QDs as ∼ 400 ps, whereas the characteristic time of intra-dot relaxation was much shorter -less than 30 ps -depending on excitation density 26,27 . Because of the rapid intra-dot relaxation, we can expect that an electron and a hole recombine after they are in quasi-equilibrium.…”
Section: B Optical Arrangementmentioning
confidence: 99%